Penerapan Bimbingan Klasikal Dalam Membentuk Kepercayaan Diri Remaja Panti Asuhan Mitra Payakumbuh - Putri, Destia; Putra, Dodi Pasila (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Classical guidance is a guidance program designed by holding face-to-face meetings with counselees, on a class basis. The aim of the research is to find out whether the application of classical guidance services is effective in shaping teenagers' personalities, one of which is self-confidence. The type of research is qualitative based on facts and results of observations in the field using power point media, the source and research subjects are the caretaker of the orphanage and group members. The results of the research state that the application of classical guidance services is effective in building the self-confidence of teenagers in orphanages. Based on the results obtained, it is known that after implementing classical guidance services there has been a good change, namely that initially the children tended to close themselves off, now they have started to try and try to open themselves up, this is because the children have received information and understanding about the impacts that will occur if they always isolating oneself from the environment, so that the implementation of group guidance is expected to be able to have a positive influence on the self-confidence of teenagers at the Mitra Payakumbuh Orphanage